The Molecular Weight Distribution of Occluded Hydrocarbon Gases in the Khibiny Nepheline–Syenite Massif (Kola Peninsula, NW Russia) in Relation to the Problem of Their Origin - Valentin A. Nivin; Vyacheslav V. Pukha; Olga D. Mokrushina; Julia A. Mikhailova (Geosciences, 2022)
The origin of hydrogen–hydrocarbon gases present in the rocks of the Khibiny massif in unusually high concentrations has been the subject of many years of discussion. To assess the role of potential mechanisms and relative time of formation of gases occluded in inclusions in minerals, the molecular weight distribution of C1–C5 alkanes in the main rock types of the Khibiny massif was studied. For this purpose, the occluded gases were extracted from rocks by mechanical grinding and their composition was analyzed on a gas chromatograph. It is established that the molecular weight distribution of occluded hydrocarbon gases in the Khibiny massif corresponds to the classical Anderson–Schulz–Flory distribution. In addition, the slopes of the linear relationships are relatively steep. This indicates a predominantly abiogenic origin of the occluded gases of the Khibiny massif. At the same time, a small proportion of biogenic hydrocarbons is present and is associated with the influence of meteoric waters. It was also found that in the Khibiny massif, the proportion of relatively high-temperature gases decreases towards the Main foidolite Ring in the following sequence: foyaite and khibinite–trachytoid khibinite–rischorrite and lyavochorrite–foidolites and apatite–nepheline ores. In the same sequence, an increase in the proportion of heavy hydrocarbons and the increasing role of oxidation and condensation reactions in the transformation of hydrocarbons occurs.